Evaluating Player Attitudes in Mobile Legends: An SFL Appraisal Analysis - Ela Martisa; Veren Karolina Bidang; Sarniati Nuru; Amiruddin Eso (EDUJ : English Education Journal, 2025)
This study investigates how Indonesian university students express evaluative meanings while playing Mobile Legends by applying the Attitude subsystem of the Appraisal Framework within Systemic Functional Linguistics (SFL). As competitive mobile games involve fast, spontaneous communication, player discourse often reflects emotional reactions, social judgments, and personal values that shape interaction quality. Using a descriptive qualitative design, data were collected from eight Mobile Legends players through written semi-structured interviews. The analysis focuses on three attitude types—affect, judgment, and appreciation—to identify how players linguistically evaluate gameplay experiences, teammates, and game elements. The findings show that affect is the most dominant evaluative resource, with players expressing excitement, frustration, stress, and satisfaction depending on match situations. Judgment appears through assessments of teammate skill, reliability, and behavior, while appreciation emerges in players’ valuation of hero design, game mechanics, and visual quality. These patterns indicate that player communication combines emotional expression, moral evaluation, and experiential value in a dynamic way consistent with the Appraisal Framework. The study contributes to Indonesian digital discourse research by demonstrating how evaluative language in gaming is systematically constructed and highlights the need for greater awareness of positive communication practices in competitive online environments.